2014
DOI: 10.1002/hbm.22683
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in cognitive regulation of psychosocial achievement stress: Brain and behavior

Abstract: Although cognitive regulation of emotion has been extensively examined, there is a lack of studies assessing cognitive regulation in stressful achievement situations. This study used functional magnetic resonance imaging in 23 females and 20 males to investigate cognitive downregulation of negative, stressful sensations during a frequently used psychosocial stress task. Additionally, subjective responses, cognitive regulation strategies, salivary cortisol, and skin conductance response were assessed. Subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 60 publications
(112 reference statements)
11
70
2
2
Order By: Relevance
“…These results supported the sex differences in self‐reported anxious symptoms as observed in general population . Indeed, females seem to be more vulnerable to stress‐ and fear‐based disorders (such as anxiety), although this is still matter of investigation . The weak negative correlation of the bulbar subdomain of the ALSFRS‐R with both state and trait anxiety supported previous evidence suggesting an association between anxious symptoms and impaired speech and swallowing functioning .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results supported the sex differences in self‐reported anxious symptoms as observed in general population . Indeed, females seem to be more vulnerable to stress‐ and fear‐based disorders (such as anxiety), although this is still matter of investigation . The weak negative correlation of the bulbar subdomain of the ALSFRS‐R with both state and trait anxiety supported previous evidence suggesting an association between anxious symptoms and impaired speech and swallowing functioning .…”
Section: Discussionsupporting
confidence: 83%
“…92,93 Indeed, females seem to be more vulnerable to stress-and fear-based disorders (such as anxiety), although this is still matter of investigation. 94,95 The weak negative correlation of the bulbar subdomain of the ALSFRS-R with both state and trait anxiety supported previous evidence suggesting an association between anxious symptoms and impaired speech and swallowing functioning. 20 The present findings could also suggest that patients experience stable and continuous concerns about their health problems when bulbar impairment arises, thus needing special psychological support.…”
Section: Discussionsupporting
confidence: 78%
“…Some review articles have suggested the possibility of sex differences in neural activation in response to emotionally salient cues (Filkowski, Olsen, Duda, Wanger, & Sabatinelli, 2017;Hamann, 2005;Stevens & Hamann, 2012), while others have found no sex differences in the processing of negative events (Garcia-Garcia et al, 2016). Kogler, Gur, and Derntl (2015) examined sex differences in stressor-evoked, neural subjective stress, skin conductance, and cortisol responses in 43 healthy adults. Results indicated women exhibited greater neural and levels of perceived stress compared to men during the stress task, but there were no sex differences in galvanic skin or cortisol responses (Kogler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The data demonstrated that although men were similar to women in the low estrogen phase, the men had significantly higher activation within the hippocampus and ACG, with the greatest effect sizes in the mPFC and OFC, relative to high estrogen women (Goldstein et al, 2010). Moreover, in a psychosocial achievement stress test, women reported feeling more stress than men, which was associated with higher activation in limbic and attention-related brain structures (Kogler et al, 2014). Together, the data in both humans and rats demonstrate sex differences not only in the effects of stress on behavior, but also in the structure and function of the neurocircuitry mediating them.…”
Section: Sex Differences In Stressmentioning
confidence: 99%
“…This sex bias may be attributed in part to a greater sensitivity to stressful and traumatic life experiences in women. Indeed, numerous studies have examined sex differences in the response to stress and have identified differences in the neural circuits that impact emotional reactivity (Goldstein et al, 2010; Kogler et al, 2014). However, how these mechanisms may be mediating sex differences in anxiety disorders remains unclear.…”
Section: Introductionmentioning
confidence: 99%